2023
DOI: 10.1097/aog.0000000000005070
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole Compared With Clomiphene Citrate for Polycystic Ovarian Syndrome

Abstract: To estimate the effect of letrozole and clomiphene citrate in women with infertility and polycystic ovarian syndrome (PCOS). METHODS OF STUDY SELECTION: MEDLINE throughPubMed, Web of Science, EMBASE, Cochrane Library, and ClinicalTrials.gov were searched for relevant studies from inception to February 1, 2022. Two reviewers retrieved, filtered, and extracted data independently using the bibliographic software EndNote X9 and Excel workbook. We included randomized controlled trials (RCTs) reporting ovulation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…We have previously presented that patients in LE group had significantly higher odds of ovulation than in CC group. In comparison of our result with previous meta-analyses, He et al [58], Tsiami et al [61] and Zhuo et al [62] reported the same result. Wang et al pointed out that the ovulation rate was significantly better when patients were taking LE instead of CC [63].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have previously presented that patients in LE group had significantly higher odds of ovulation than in CC group. In comparison of our result with previous meta-analyses, He et al [58], Tsiami et al [61] and Zhuo et al [62] reported the same result. Wang et al pointed out that the ovulation rate was significantly better when patients were taking LE instead of CC [63].…”
Section: Discussionsupporting
confidence: 90%
“…We found that the odds of pregnancy were significantly higher in patients treated with letrozole than in CC group. In comparison of our result with previous meta-analyses, four were found to have significantly higher pregnancy rates [59, 6264] and three were reported to have significantly higher odds of live birth [6264] after letrozole treatment. Gadalla et al [11] and Hu et al [65] described similar differences between the two groups.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, LTZ has been claimed as more effective than CC in achieving better pregnancy rates and live birth rates as reported by Sakar and Oglak 2020; [ 18 ]. A meta-analysis by Liu et al 2023; reported similar findings but the authors concluded that there is still mixed quality of evidence [ 28 ]. According to Chi-square and logistic regression analysis in this study, no association was observed between the outcome measures and the patients’ clinical parameters which supports eliminating the confounding factors that may influence the efficacy of the two drugs.…”
Section: Discussionmentioning
confidence: 98%
“…In a Zhuo Liu et al study, pooled analysis indicated that letrozole treatment prevailed against clomiphene citrate in ovulation rate (RR 1.14, 95% CI 1.06-1.21, P <.001), clinical pregnancy rate (RR 1.48, 95% CI 1.34-1.63, P <.001), and live-birth rate (RR 1.49, 95% CI 1.27-1.74, P <.001) [32].…”
Section: Ovulation Inducersmentioning
confidence: 95%